Effect of Intramuscularly Administered Oxytetracycline or Enrofloxacin on Vancomycin-Resistant Enterococci, Extended Spectrum Beta-Lactamase- and Carbapenemase-Producing Enterobacteriaceae in Pigs - Elena González-Fandos; Alba Martínez-Laorden; Ana Abad-Fau; Eloisa Sevilla; Rosa Bolea; María Jesús Serrano; Olga Mitjana; Cristina Bonastre; Alicia Laborda; María Victoria Falceto; Rafael Pagán (Animals, 2022)
Nowadays, there is a great concern about the prevalence of multidrug resistant Enterococcus spp. and Enterobacteriaceae in food-producing animals. The aim of this work was to evaluate the effect of oxytetracycline or enrofloxacin treatment on vancomycin-resistant enterococci (VRE), extended spectrum β-lactamase (ESBL) and carbapenemase-producing Enterobacteriaceae in pigs. A total of 26 piglets were received and distributed in three groups. Group 1 was treated with enrofloxacin (N = 12), group 2 with oxytetracycline (N = 10) and group 3 did not receive any treatment (control group) (N = 4). A higher number of vancomycin-resistant E. faecium were recovered compared to E. faecalis. In the pigs treated with enrofloxacin, vancomycin resistant E. faecium was found in a higher percentage of animals than in the control group. ESBL-producing E. coli was not detected in rectal samples from control animals. However, it was detected in 17–20% of animals treated with oxytetracycline on days 6 to 17 and in 17–50% of the animals treated with enrofloxacin. Carbapenemase-producing E. coli was isolated in animals treated with oxytetracycline, but not in animals treated with enrofloxacin or in the control group. This study highlights that the use of oxytetracycline or enrofloxacin in food-producing animals could select ESBL and carbapenemase-producing E. coli. Further studies shall be needed to validate the results obtained, considering a more robust and extended experimental design.